The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/aem.01719-15
|View full text |Cite
|
Sign up to set email alerts
|

Botrytis pseudocinerea Is a Significant Pathogen of Several Crop Plants but Susceptible to Displacement by Fungicide-Resistant B. cinerea Strains

Abstract: cBotrytis cinerea is one of the most important pathogens worldwide, causing gray mold on a large variety of crops. Botrytis pseudocinerea has been found previously to occur together with B. cinerea in low abundance in vineyards and strawberry fields. Here, we report B. pseudocinerea to be common and sometimes dominant over B. cinerea on several fruit and vegetable crops in Germany. On apples with calyx end rot and on oilseed rape, it was the major gray mold species. Abundance of B. pseudocinerea was often nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 41 publications
2
66
0
Order By: Relevance
“…Resistance to benzimidazoles was also very common, even though this fungicide has not been in use for many years. Genetic characterization with species-specific PCR primers (Plesken et al, 2015a) revealed eight isolates to belong to B. pseudocinerea ; six of them were sensitive to all fungicides and two were resistant only to benzimidazoles. Isolates belonging to B. cinerea groups N and S showed a random distribution, with no evidence of any host preference or differences in fungicide resistance frequencies (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance to benzimidazoles was also very common, even though this fungicide has not been in use for many years. Genetic characterization with species-specific PCR primers (Plesken et al, 2015a) revealed eight isolates to belong to B. pseudocinerea ; six of them were sensitive to all fungicides and two were resistant only to benzimidazoles. Isolates belonging to B. cinerea groups N and S showed a random distribution, with no evidence of any host preference or differences in fungicide resistance frequencies (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Formerly thought to be caused by one species called Botrytis cinerea Pers. :Fr., gray mold is now known to be due to a complex of cryptic species (Walker et al, 2011; Plesken et al, 2015a). In addition, the core species of B. cinerea can be separated into genetically more or less distinct groups (N and S) which were shown to be enriched differentially in response to fungicide treatments (Leroch et al, 2013; Plesken et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates possessing the P225L and P225T mutations were originating from Germany. All the isolates were identified as B. cinerea using a duplex PCR assay developed by Plesken et al (2015). A complete list of the isolates used in the study and their origin is provided in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Botrytis pseudocinerea appears, like B. cinerea, to have a wide host range but is subject to replacement by fungicide-resistant strains of B. cinerea, and appears to produce fungicide-resistant strains less frequently than B. cinerea (Plesken et al 2015). Both host range and fungicide susceptibility/resistance play strong roles in disease management.…”
Section: Case Summariesmentioning
confidence: 99%